An Analysis of Talent Management Implementation from a Merit System Perspective: A Case Study of the Secretariat General of the People’s Consultative Assembly of the Republic of Indonesia - Desvaliana, Vuty; Muslim, Muh. Azis (Journal Research of Social Science, Economics, and Management, 2026)
This study analyzes the implementation of talent management from a merit system perspective at the Secretariat General of the People’s Consultative Assembly of the Republic of Indonesia. The background of this research lies in the increasing need for professional, accountable, and adaptive human resources in public organizations amid bureaucratic reform. The study aims to examine the actual implementation of talent management, identify its challenges, and formulate strategies to accelerate its execution within a merit-based framework. Using a post-positivist paradigm with a descriptive qualitative approach, data were collected through in-depth interviews, document analysis, and literature studies, validated by triangulation of sources and data. The findings show that the institution has established a comprehensive policy framework and guidelines supported by a digital platform and competency assessment system. However, implementation remains suboptimal due to weak data integration, insufficient managerial commitment, and limited meritocratic culture. The study identifies four key influencing dimensions cultural, managerial, human resources, and environmental where leadership consistency and organizational culture transformation are critical. It concludes that although the Secretariat General has developed a strong conceptual foundation, the full institutionalization of merit-based talent management requires stronger leadership commitment, integrated data systems, and alignment between organizational strategy and human capital development.